Improving weathering performance of wood by borates impregnation and liquid glass coating : Poboljšanje otpornosti drva na vremenske utjecaje impregnacijom boratima i premazom od tekućeg stakla - Kucuktuvek, Mustafa (Array, 2020)
Weathering performance of impregnated and coated wood products is an important issue that influences their appearance as well as their service life after outdoor or indoor exposure. A novel procedure to improve the weathering performance of Scots pine wood (Pinus sylvestris L.) is proposed in this study. Wood samples were impregnated with ammonium tetrafluoroborate (ATFB), ammonium pentaborate (APB) and boric acid (BA), and afterward coated with a layer of liquid glass (LG). Surface hardness, color changes, and surface roughness of wood samples were investigated after 250 h and 500 h of exposure to artificial weathering. The results revealed that, except for untreated (control), all other treatment groups caused an increase in surface hardness of Scots pine after weathering. A decrease in the CIE L* value corresponds to the darkening of samples after weathering. Borates-impregnated and LG-coated Scots pine samples possessed the highest color stability. However, all treatment combinations resulted in reddish and yellowish tones after weathering. Exposure to weathering increased surface roughness of wood samples. The surface roughness of the untreated (control) group was higher than that of impregnated and coated samples.